Kyanite-bearing anatectic metapelites from the Eastern Himalayan Syntaxis, Eastern Tibet, China : textural evidence for partial melting and phase equilibria modeling - Guilmette, Carl; Aphrodite, Indares; Réjean, Hébert; Wang, CS (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1258 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.56